Is Quiz Competition an Effective Promotional Tool for Marketing Online Databases?: A Case Study in Universiti Sains Malaysia Library - Ahmat, Muhammad Akmal (Faculty of Information Management, Universiti Teknologi MARA, 2014)
This paper focuses on a case study to determine the impact of quiz competition as an effective promotion tool for marketing online databases in Universiti Sains Malaysia (USM) Library. The quiz competition was promoted using Plan, Do,Check and Action (PDCA) tool and described briefly. Then, the study tried to make a comparison analysis based on the database statistics usage before and after the quiz competition was introduced. Two samples of databases showed an increase in statistics usage while one sample showed a decrease. The participants’ level of satisfaction for the questions in the competition and for the prizes offered was also studied using simple structured interview. This study is hoped to serve as an example of case study to show that promotion through quiz competition might help librarians to persuade the patrons to notice more about the importance of using online databases and indirectly create intangible mutual understanding among the librarians, patrons, and database vendors.